Electro-Static Discharge Reduction in Silicone Filter Process using Faraday Cage with Ground Technique - Lertlam, Krit; Photong, Chonlatee (Engineering and Technology Horizons, 2021)
This research aims to reduce electro-static discharge and increase safety for workers in the silicone filling process by using the Faraday cage technique. The research found that the electro-static and its discharge occurred rapidly and severely, which was caused by the friction of triboelectric series material, silicone, and nylon filter cloth, that was compressed by very high compression of 150-200 bars. This electro-static discharge was therefore dangerous for the workers. This research proposes design and construction of an equipment set to eliminate the problem. The experimental test scenarios were divided into 3 cases: without the Faraday cage, with the Faraday cage but without grounding and with Faraday cage with grounding. According to the research results, it was found that by installing the Faraday cage solely could reduce the amount of electro-static discharge by 51% but with also the additional grounding could reduce the amount of electro-static by 71 % when grounded, compared to one without the Faraday cage.